Simplify the Following Expressions: (11 + Sqrt11)(11 - Sqrt11) - Mathematics

Advertisements
Advertisements

Simplify the following expressions:

`(11 + sqrt11)(11 - sqrt11)`

Advertisements

Solution

We know that `(a + b)(a - b) = a^2 - b^2` We will use this property to simplify the expression

`(11 + sqrt11)(11 - sqrt11)`

`∴ (11 + sqrt11)(11 - sqrt11) = 11^2 - (sqrt11)^2`

`= 11 xx 11 - sqrt11 xx sqrt11`

`= 121 - sqrt(11 xx 11)`

`= 121 - (11^2)^(1/2)`

= 121 - 11

= 110

Hence the value of expression is 110.

  Is there an error in this question or solution?
Chapter 3: Rationalisation - Exercise 3.1 [Page 2]

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 3 Rationalisation
Exercise 3.1 | Q 3.1 | Page 2

Video TutorialsVIEW ALL [1]

Share
Notifications



      Forgot password?
Use app×